Promiscuous activity of 3‐isopropylmalate dehydrogenase produced at physiological level affords Escherichia coli growth on d‐malate. Issue 15 (2nd June 2020) - Khan, Mohammad Shahneawz; Gargiulo, Serena; Soumillion, Patrice
Abstract : Promiscuous activities of enzymes may serve as starting points for the evolution of new functions. However, most experimental examples of promiscuity affording an observable phenotype necessitate the artificial overexpression of the target enzyme. Here, we show that 3‐isopropylmalate dehydrogenase (IPMDH), an enzyme involved in leucine biosynthesis, has a secondary activity on d ‐malate, which is sufficient for d ‐malate assimilation under physiological conditions where the enzyme is upregulated. In vitro, the turnover constant ( k cat ) of IPMDH for d ‐malate is about 30‐fold lower than the k cat for 3‐isopropylmalate, yet sufficiently high to support the growth on d ‐malate. From an evolutionary perspective, our results highlight the possibility of phenotype emergence triggered by arbitrary changes in environmental conditions and prior to any mutational event. Abstract :